Transition of Crypto Asset Supervision From Bappebti to OJK - Soerjadi, Diadjeng Famelia; Kusmiadi, Rossella (Ridwan Institute, 2024)
This article discusses the impact of rapid technological advancements in information and communication on the financial system, particularly the shift from cash-based transactions to non-cash payment methods and the emergence of cryptocurrencies. The increased adoption of digital currencies, such as Bitcoin and Ethereum, highlights the need for a comprehensive regulatory framework to ensure investor protection and financial stability. This study focuses on the role of Indonesia’s Financial Services Authority (OJK) in regulating cryptocurrencies, especially following the enactment of Law No. 4 of 2023, which mandates OJK’s involvement in overseeing these digital assets. The research utilizes a normative legal approach, leveraging a literature review to gather relevant literature, regulations, and legal frameworks on cryptocurrency management. Key findings reveal the existence of a dual regulatory framework involving both OJK and the Commodity Futures Trading Regulatory Agency (Bappebti), which may lead to potential conflicts and challenges in supervision. This article aims to provide recommendations for regulatory harmonization between OJK and Bappebti to enhance regulatory effectiveness and protect investors in the rapidly evolving cryptocurrency landscape. Through this analysis, the study seeks to contribute to a deeper understanding of the regulatory challenges faced by cryptocurrencies and propose policy solutions that can strengthen OJK’s role in this sector..